2020
DOI: 10.3390/ijerph17061878
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mediation Roles of Child Screen-Viewing between Parental Factors and Child Overweight in Taiwan

Abstract: Children’s screen-viewing behavior is influenced by parents’ own screen-viewing hours and the parental rules set for screen-viewing time. However, whether childhood obesity is associated with these three factors has not been widely investigated in Chinese populations. We examined the relationships between parental rules, parental screen-viewing, child screen-viewing and child overweight. Questionnaires were distributed to 1300 parents who had children studying in two elementary schools in an eastern Taiwanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Lastly, some important confounding variables could not be controlled in the present study. Specifically, schoolchildren’s screen behaviors are highly associated with their parents’ screen behaviors [ 57 , 58 ]. However, we did not collect information regarding parents’ screen use.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, some important confounding variables could not be controlled in the present study. Specifically, schoolchildren’s screen behaviors are highly associated with their parents’ screen behaviors [ 57 , 58 ]. However, we did not collect information regarding parents’ screen use.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Chinese primary school children also showed the mediating role of children’s screen-viewing time in the association between parental screen-viewing and children being overweight. A study by Lin et al showed that parents decreasing their screen time effectively decreases children’s screen-viewing time, which has an influence on children’s weight status [ 36 ]. In addition, besides the preschool environment, the home environment is a setting where preschool children spend most of their time [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the importance of knowing the perspectives of parents regarding physical activity is underlined, as parents can play a crucial role in determining their children’s sedentary behaviors. Two recent studies in Asia [ 54 , 55 ] showed the mutually interdependent relationship between parents’ and children’s physical activity and screen-viewing behaviors, highlighting the impact on children’s health. The results show the potential mechanistic link between parents’ perspectives on physical activities and children’s health outcomes, showing that parents’ screen-viewing behaviors and rules may be associated with their children’s insufficient physical activity levels and overweight problems.…”
Section: Discussionmentioning
confidence: 99%